PERENCANAAN STRATEGIS, ANGGARAN DAN KINERJA KEUANGAN - Herold Moody Manalu (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2019)
This study aimed to determine the effect of strategic planning and budgeting to financial performance. The population in this study were faculty and supporting staff at Bandung Adventist School. The research sample using a saturated sample of 56 respondents, the instrument used was a questionnaire’s. Method of analysis used was a regression. The results showed the correlation coefficient r = 0.507, where the relationship between variables was positive and the coefficient determination by 25,7%, and as much as 74.3% by the other factors. The result suggests strategic planning and budgeting has a significant effect on financial performance by P-value 0.000 < 0.05